In Vivo and In Vitro Analysis in Coronary Artery Disease Related to Type 2 Diabetes - Infante, Teresa; Forte, Ernesto; Aiello, Marco; Salvatore, Marco; Cavaliere, Carlo (Frontiers in Endocrinology, 2017)
AIM: The leading cause of morbidity and mortality in patients with type 2 diabetes (DM) is coronary artery disease (CAD), a condition often asymptomatic but severe in these patients. Although glucose metabolism impairment and oxidative stress are known actors in the endothelial dysfunction/remodeling that occurs in diabetic patients, the relationship between cardiovascular disorders and DM is not fully understood. We have performed both an in vivo imaging and in vitro molecular analysis to investigate diabetic-specific CAD alterations. METHODS: Computed tomography coronary angiography (CTCA) was performed in a group of 20 diabetic patients with CAD (DM+CAD+), 20 non-diabetic with CAD (DM-CAD+), 10 diabetic non-CAD patients (DM+CAD-), and 20 non-diabetic healthy subjects (HS). Imaging quantitative parameters such as calcium score (Cascore), calcified plaque volume (CPV), non-calcified plaque volume (NCPV), total plaque volume (TPV), remodeling index (RI) and plaque burden were extracted for each CAD subject. Moreover, the expression levels of Superoxide dismutase 2 (SOD2) and Liver X receptor alpha (LXRα) genes were analyzed in the peripheral blood mononuclear cells, whereas Hyaluronan (HA) concentrations were evaluated in the plasma of each subject. RESULTS: Imaging parameters, such as Cascore, CPV, RI and plaque burden were significantly higher in DM+CAD+ group, compared to DM-CAD+ (P=0.019; P=0.014; P<0.001, P<0.001 respectively). SOD2 mRNA was down-regulated while LXRα gene expression was up-regulated in DM+CAD-, DM+CAD+ and DM-CAD+ groups compared to HS (P=0.001, P=0.03 and P=0.001 for SOD2 and P=0.006, P=0.008 and P<0.001 for LXRα, respectively). Plasmatic levels of HA were higher in DM-CAD+, DM+CAD- and DM+CAD+ groups, compared to HS (P=0.001 for the three groups). When compared to DM-CAD+, HA concentration was higher in DM+CAD- (P=0.008) and DM+CAD+ (P<0.001) with a significant difference between the two diabetic groups (P=0.003). Moreover, HA showed a significant association with diabetes (P=0.01) in the study population and the correlation between HA levels and glycemia was statistically significant (ρ=0.73, P<0.001). CONCLUSION: In our population, imaging parameters highlight a greater severity of CAD in diabetic patients. Among molecular parameters, HA is modulated by diabetic CAD related alterations while SOD2 and LXRα are found to be more associated to CAD but do not discriminate between